Olfactory functional covariance connectivity in Parkinson’s disease: Evidence from a Chinese population - Du, Shouyun; Wang, Yiqing; Li, Guodong; Wei, Hongyu; Yan, Hongjie; Li, Xiaojing; Wu, Yijie; Zhu, Jianbing; Wang, Yi; Cai, Zenglin; Wang, Nizhuan (Frontiers in Aging Neuroscience, 2023)
Introduction Central anosmia is a potential marker of the prodrome and progression of Parkinson’s disease (PD). Resting-state functional magnetic resonance imaging studies have shown that olfactory dysfunction is related to abnormal changes in central olfactory-related structures in patients with early PD. Methods This study, which was conducted at Guanyun People’s Hospital, analyzed the resting-state functional magnetic resonance data using the functional covariance connection strength method to decode the functional connectivity between the white–gray matter in a Chinese population comprising 14 patients with PD and 13 controls. Results The following correlations were observed in patients with PD: specific gray matter areas related to smell (i.e., the brainstem, right cerebellum, right temporal fusiform cortex, bilateral superior temporal gyrus, right Insula, left frontal pole and right superior parietal lobule) had abnormal connections with white matter fiber bundles (i.e., the left posterior thalamic radiation, bilateral posterior corona radiata, bilateral superior corona radiata and right superior longitudinal fasciculus); the connection between the brainstem [region of interest (ROI) 1] and right cerebellum (ROI2) showed a strong correlation. Right posterior corona radiation (ROI11) showed a strong correlation with part 2 of the Unified Parkinson’s Disease Rating Scale, and right superior longitudinal fasciculus (ROI14) showed a strong correlation with parts 1, 2, and 3 of the Unified Parkinson’s Disease Rating Scale and Hoehn and Yahr Scale. Discussion The characteristics of olfactory-related brain networks can be potentially used as neuroimaging biomarkers for characterizing PD states. In the future, dynamic testing of olfactory function may help improve the accuracy and specificity of olfactory dysfunction in the diagnosis of neurodegenerative diseases.